Good Corporate Governance and Corporate Social Responsibility on Financial Performance Through Earning Management - Supriyanto, Supriyanto; Novriyanti, Novriyanti (Jurnal Akuntansi, 2024)
Abstract Purpose - This study aims to determine the effect of GCG and CSR on Financial Performance Through Earning Management during Covid-19 pandemic to see whether the company can be sustainable. Design/methodology/approach - Study employs a quantitative methodology and utilizes the firm LQ45, one of 45 companies listed on the IDX for the 2018–2022 time frame. Based on EPS and TBQ as proxies.Findings - The research findings demonstrate a substantial impact of CSR on FP. Financial performance is significantly impacted by GCG factors with institutional ownership proxies, ROA, EPS, and TBQ proxies, as well as audit quality indicators. The Kind variable on financial performance, which is mediated by the total accrual of the CSR variable in the form of TBQ and EPS, can't be mediated by Total Accrual. This indicates that the independent variable has no discernible negative impact on financial performance. Total accruals mediate between the independent variable's large positive impact on financial performance. Thus, it is clear that whereas earnings management can do so between GCG and CSR variables to financial performance. Management can choose to either maximize or minimize income through accounting policies, which can worry investors. Hence, enhancing environmental and social activities through CSR can impact earnings management.Research limitations/implications – Implementing CSR in businesses can safeguard the environment while also improving financial success, Especially given that the ordinary investor is concerned with the environment and the company's sustainability. Keywords: Good Corporate Governance, Corporate Social Responsibility, Earning Management, Financial Performance, and Audit Quality